Oceanographic conditions around the Galápagos Archipelago and their influence on cetacean community structure - Palacios, Daniel Mauricio
The objectives of this dissertation were to describe the complex oceanographic conditions around the Galápagos Archipelago (eastern equatorial Pacific), their seasonal variability, and their effects on patterns of cetacean occurrence. The physical and ecological factors leading to a plume of high phytoplankton biomass in the wake of the Galápagos were investigated with principal component and regression analyses of water-column climatologies and satellite-derived ocean color. The results supported the notion that this "island-mass effect" is fueled by upwelling of the Equatorial Undercurrent (EUC) combined with natural iron enrichment from the island platform. Seasonal variability in long-term monthly fields of satellite-derived sea-surface temperature and ocean color was studied through harmonic analysis and empirical orthogonal function decomposition. Two annual cycles were identified in both variables. The intensification of the Equatorial Front and the South Equatorial Current in the second part of the year was the dominant signal in the data. A secondary cycle reaching its peak in the first part of the year was associated with the topographically induced upwelling of the EUC on the western side of the archipelago, and with advection of upwelled Panama Bight water on the eastern side. The occurrence of nine cetacean Species (including seven small and medium-sized delphinids, the sperm whale, and the Bryde's whale) in relation to environmental variability around the archipelago was described. Seasonally persistent sectors of the archipelago characterized by the presence of distinct species assemblages of stratified, upwelling, and nearshore environments were identified through cluster and indicator species analysis. The dominant pattern in species distribution, as extracted by a nonmetric multidimensional scaling procedure, was well correlated with the main environmental gradient (described by the degree of water-column stratification, chlorophyll-a concentration, and distance from the islands). The ...